THE CREATION OF A DANCE FROM THE INSPIRATION OF GANESHA AND HIS SIX DUTIES - Acalasawamak, Ruksiney (Fine Arts Journal: Srinakharinwirot University, 2025)
Background and Objectives: The meanings and belief in Thai context regarding Ganesha to inspiration in creative of dance. The objectives of this research were to study the meanings and beliefs in Thai context regarding Ganesha and his six duties, and to create dance movements inspired by Ganesha and his six duties. Methods: The research methodology combined creative research and qualitative research approaches. The research tools consisted of documentary data, stakeholder interviews, observations, experimental dance creation process, and researcher’s personal experience. Key Findings: Research findings revealed that: 1.Regarding the meanings and beliefs in Thai context about Ganesha and his six duties, from past to present, Ganesha has served as both spiritual anchor and symbolic figure representing his characteristics: He is supreme over obstacles, the remover of obstacles, the creator, the possessor of wisdom, the protector, the benevolent one, the dutiful son who worships Shiva, and one worthy of reverence. Therefore, the meanings according to his characteristics studied in this research can be summarized into six duties: He is the remover of obstacles, the bestower of wisdom, the protector, the grantor of success, the embodiment of filial piety, and one worthy of reverence. 2. The creation of dance movements inspired by Ganesha and his six duties was developed through the researcher’s analysis of components including performance narrative or conceptual framework and dance movement design. Performance Concept or Framework: He is the remover of obstacles, the bestower of wisdom, the protector, the grantor of success, the embodiment of filial piety, and one worthy of reverence - these aspects served as guidelines for dance movement design. Dance Movement Design: The movement design in dance that has been mentioned involves choreography using direction, form, and space to reflect the intended message for audience comprehension during the performance. Implications of the Study: The research can be summarized in the following points: 1. Development of Creative Thinking in Thai Dance Choreography Design: The creation of a dance performance is achieved through a thought process and an analysis of performance design. Sometimes the performance script does not need to adhere to storytelling or complex interpretation. The presentation can, at times, use words or phrases in designing choreography. In this research, six aspects are identified: being the obstacle remover, being the wisdom giver, being the protector, being the grantor of success, being the grateful one, and being the valuable one worthy of respect. Words or phrases are used in designing the movement choreography so that they reflect the concepts identified in this research. 2. Presentation of Space Diversity in Creative Dance Performance: In this research, the presentation of spatial diversity focuses on how the performance space is utilized. For example, when depicting obstacles and problems, the researcher uses the corners of the room to represent challenges we cannot solve, like being cornered. Meanwhile, to show obstacle removal, dancers can move from the corners freely in straight lines along the walls before moving to the center. This transition into circular patterns, both small and large, symbolizes the growth of wisdom - like the process of learning and awakening. The movement itself resembles a blooming lotus, akin to someone who has attained enlightenment. The movement progresses upward from the floor, and the use of performance space expands from small circles to wider circles, etc. Conclusions and Future Study: This research focuses on the development of creativity in the movement process. The study guidelines for future research should study the creation of movement with digital media to find the Diversity in Creative Dance Performance.